Interaction between supraoptic nucleus and septal area in the control of water, sodium intake and arterial blood pressure induced by injection of angiotensin II - Saad, W. A.; Camargo, L. A. D.; Guarda, I. F. M. S.; Santos, T. A. F. B. dos; Guarda, R. S.; Simoes, S.; Rodrigues, J. A. (Elsevier B.V., 2004)
We investigated the effects of injection into the supraoptic nucleus (SON) of losartanand PD 123319 (nonpeptide AT(1) and AT(2)- angiotensin II [ANG II] receptor antagonists, respectively); d(CH2)(5)-Tyr(Me)-AVP (AVPA; an arginine-vasopressin [AVP] V-1 receptor antagonist), FK 409 (a nitric oxide [NO] donor), and N-W-mtro-(L)-arginine methyl ester ((L)-NAME; an NO synthase inhibitor) oil water intake, sodium chloride 3% (NaCl) intake and arterial blood pressure induced by injection of ANG 11 into the lateral septal area (LSA). Mate Holtzman rats (250-300 g) were implanted with cannulae into SON and LSA unilaterally. The drugs were injected in 0.5 mul over 30-60 s. Controls were injected with a similar volume of 0.15 M NaCl. ANG II was injected at a dose of 10 pmol. ANG II antagonists and AVPA were injected at doses of 80 nmol. FK 409 and (L)-NAME were injected at doses of 20 and 40 mug, respectively. Water and NaCl intake was measured over a 2-h period. Prior administration of losartan into the SON decreased water and NaCl intake induced by injection of ANG II. While there was a decrease in water intake, ANG II-induced NaCl intake was significantly increased following injection of AVPA. FK 409 injection decreased water intake and sodium intake induced by ANG II. L-NAME alone increased water and sodium intake and induced a pressor effect. (L)-NAME-potentiated water and sodium intake induced by ANG II. PD 123319 produced no changes in water or sodium intake induced by ANG II. The prior administration of losartan or AVPA decreased mean arterial pressure (MAP) induced by ANG II. PD 123319 decreased the pressor effect of ANG II to a lesser degree than losartan. FK 409 decreased the pressor effect of ANG II while (L)-NAME potentiated it. These results suggest that both ANG II AT, and AVP V, receptors and NO within the SON may be involved in water intake, NaCl intake and the pressor response were induced by activation of ANG II receptors within the LSA. These results do not support the involvement of LSA AT(2) receptors in the mediation of water and NaCl intake responses induced by ANG II, but influence the pressor response. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: angiotensin II AT(1), AT(2) receptors; arginine vasopressin V-1 receptors; nitric oxide CNS; electrolytic; cardiovascular balance